Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Motivasi pada UMKM di Kelurahan Bojong Sari Depok Jawa Barat - Rusilowati, Umi; Mukrodi, Mukrodi; Subarto, Subarto (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in driving the local economy, especially in suburban areas like Bojong Sari, Depok, West Java. However, many MSME actors still face challenges in managing human resources effectively, which impacts their motivation and business performance. This community service activity aims to enhance the understanding and application of Human Resource Management (HRM) practices to improve motivation among MSME actors in Bojong Sari. The activity was conducted on March 16, 2025, at the Bojong Sari Sub-district Office by 17 lecturers from the Master of Management Program at Pamulang University. A total of 27 local MSME business owners participated in the event. The methods employed included material presentation, simulation, group discussions, and Q&A sessions. The topics covered ranged from HR planning, employee motivation techniques, leadership styles, and performance appraisal strategies tailored for small-scale businesses. The results showed a positive response from the participants, with increased awareness and enthusiasm to implement HRM practices in their daily business operations. Participants expressed greater motivation and confidence in managing their teams more effectively. This PKM initiative demonstrates that structured HRM education can significantly contribute to strengthening the performance and sustainability of MSMEs.